Severe Acute Respiratory Syndrome Coronavirus 2 Infection is Associated with Homocysteine Level and Clinical Outcomes in Ischemic Stroke Patients - Syahrul, Syahrul; Imran, Imran; Musadir, Nasrul; Mutiawati, Vivi Keumala (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Since its emergence in December 2019 and declared as pandemic in March 2020, the drastic increase in cases of coronavirus disease 2019 (COVID-19) is alarming the importance of disease monitoring in order to prevent further complication, like ischemic stroke. One of the efforts is utilizing biomarker. For instance, elevated homocysteine level, already known risk factor of ischemic stroke, is currently identified in COVID-19 patients. AIM: To assess factor associated with homocysteine level and clinical outcomes of ischemic stroke patients. Methods: A cross-sectional study was conducted at Dr. Zainoel Abidin Hospital di Indonesia between March and August 2021. Ischemic stroke patients who had physical and neurology examinations, SARS-CoV-2 RT-PCR swab, chest x-ray, electrocardiography, head CT-scan and the total homocysteine level were included. To assess the factors associated with homocysteine level and the outcomes of ischemic stroke patients, the independent Student t-test or Anova and chi-squared were used, respectively. RESULTS: We included 62 ischemic stroke patients of which 32 (51.6%) were male and the age ranged between 30 and 80 years. Out of total, 60 patients (96.8%) were survived after the hospital admission. There was a significant association between gender and having COVID-19 with homocysteine level (p=0.012 and p=0.020, respectively). Having COVID-19 was the only variable significantly associated with the outcome of the ischemic stroke patient (p=0.035). CONCLUSION: COVID-19 is associated with homocysteine level and the clinical outcome in ischemic stroke patients. Therefore, SARS-CoV-2 infection in ischemic stroke or vice versa need to be monitored closely in hospital settings.